2022
DOI: 10.3389/fdmed.2022.864406
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Ligament Cells Are Involved in the Formation of Intracanal Cementum-Like Tissue After Regenerative Endodontic Procedures: A Mouse in situ Model

Abstract: Regenerative endodontic cell-homing procedures are frequently performed on injured immature teeth diagnosed with pulp necrosis and/or apical periodontitis. The representative histological finding after those procedures is cementum-like tissues filling in the root canal but details of the healing process remain unknown. We investigated that healing process histologically using a mouse in situ model. Regenerative endodontic procedures were experimentally performed on noninfected maxillary first molars of 6-week-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Another research group recently presented their findings on experimentation with REPs in immature mouse teeth [59]. Their data also demonstrated the feasibility of REPs in immature teeth from mice with open apexes, and their histological findings through H&E staining were similar to those obtained in the present work.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Another research group recently presented their findings on experimentation with REPs in immature mouse teeth [59]. Their data also demonstrated the feasibility of REPs in immature teeth from mice with open apexes, and their histological findings through H&E staining were similar to those obtained in the present work.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we demonstrated that an REP was achievable in mature mouse molars and that the local transplantation of DPCs improved the outcomes of REPs by promoting the formation of odontoblast-like cells and enhancing vasculogenesis. In terms of methodology, the procedure itself could be regarded as successful since REP and/or REP + DPC treatment led to new tissue formation inside the canals of mature mouse molars, similar to the healing responses observed in previous preclinical studies using the mature molars of larger animals [57,58] and immature mouse molars [59]. Furthermore, the lack of periapical lesions or root resorption in almost all samples in the µCT data supports this hypothesis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation